Repeated social defeat in male mice induced unique RNA profiles in projection neurons from the amygdala to the hippocampus - Rebecca G. Biltz; Wenyuan Yin; Ethan J. Goodman; Lynde M. Wangler; Amara C. Davis; Braedan T. Oliver; Jonathan P. Godbout; John F. Sheridan (Brain, Behavior, & Immunity - Health)
Chronic stress increases the incidence of psychiatric disorders including anxiety, depression, and posttraumatic stress disorder. Repeated Social Defeat (RSD) in mice recapitulates several key physiological, immune, and behavioral changes evident after chronic stress in humans. For instance, neurons in the prefrontal cortex, amygdala, and hippocampus are involved in the interpretation of and response to fear and threatful stimuli after RSD. Therefore, the purpose of this study was to determine how stress influenced the RNA profile of hippocampal neurons and neurons that project into the hippocampus from threat appraisal centers. Here, RSD increased anxiety-like behavior in the elevated plus maze and reduced hippocampal-dependent novel object location memory in male mice. Next, pan-neuronal (Baf53 b-Cre) RiboTag mice were generated to capture ribosomal bound mRNA (i.e., active translation) activated by RSD in the hippocampus. RNAseq revealed that there were 1694 differentially expressed genes (DEGs) in hippocampal neurons after RSD. These DEGs were associated with an increase in oxidative stress, synaptic long-term potentiation, and neuroinflammatory signaling. To further examine region-specific neural circuitry associated with fear and anxiety, a retrograde-adeno-associated-virus (AAV2rg) expressing Cre-recombinase was injected into the hippocampus of male RiboTag mice. This induced expression of a hemagglutinin epitope in neurons that project into the hippocampus. These AAV2rg-RiboTag mice were subjected to RSD and ribosomal-bound mRNA was collected from the amygdala for RNA-sequencing. RSD induced 677 DEGs from amygdala projections. Amygdala neurons that project into the hippocampus had RNA profiles associated with increased synaptogenesis, interleukin-1 signaling, nitric oxide, and reactive oxygen species production. Using a similar approach, there were 1132 DEGs in neurons that project from the prefrontal cortex. These prefrontal cortex neurons had RNA profiles associated with increased synaptogenesis, integrin signaling, and dopamine feedback signaling after RSD. Collectively, there were unique RNA profiles of stress-influenced projection neurons and these profiles were associated with hippocampal-dependent behavioral and cognitive deficits.